Satisfaction with travel and residential self-selection: How do preferences moderate the impact of the Hiawatha Light Rail Transit line? - Cao, Jason; Ettema, Dick (Journal of Transport and Land Use, 2014)
Policies in urban and transportation planning increasingly aim at improving residents’ wellbeing. Satisfaction with travel (SWT) is a relevant component of well-being. Insight into the effect of the built environment on SWT is limited and therefore the focus of this paper. To assess this effect, a crucial issue is to what extent a relationship between the built environment and SWT is due to residential self-selection. To explore this question, a survey was held in corridors of the Twin Cities, which differed in terms of accessibility and transit options. Respondents reported their SWT, travel preferences and reasons for location choices,among other things. Using a fixed-effect model of SWT, we found that self-selection plays a significant role in explaining SWT, but that built environment characteristics also have an independent effect on SWT. Taken together this suggests that policies to build high-quality transit have a positive effect on SWT, in general, and particularly for those with a transit preference.